REAKSI PASAR MODAL INDONESIA PASKA PENGUMUMAN PAKET KEBIJAKAN EKONOMI JILID XVI PADA SAHAM YANG TERDAFTAR PADA INDEKS LQ 45 - Fathan Adhi Thirafi (2020)
In investing, the orientation of the investors must be highest profit from the investation that they made. There's so much indicator that can be used to predict the trend of stock like stock return, trading volume, bid-ask spread, etc. The trading Volume is one of the main factors or the first indicator can be used to predict the trend of a stock.This quantitative study that used Lagrance Multiplier metode aims to determine the relationship between trading volumes as dependent variable and return stock, inflation, and BI 7 Days Rate as independent variables after the announcement of the economic policy package of XVI volumes.The study was held on 19 November 2018 (after the announcement of the economic policy package of XVI volumes) until 30 July 2019.The results of this research show that 1) Return of shares has no effect on the trading volume. 2) Inflation positively affects the volume of trade. 3) BI 7 Days Rate positively affects the trading volume.